Effectiveness of a Family Self-management Enhancement Program for Suspected Diabetic Patients in Chaiyaphum Province - Chotnawakun, Somkid; Moolsart, Sutteeporn; Sakunhongsophon, Somnuk (Journal of Thailand Nursing and Midwifery Council, 2025)
Introduction Diabetes is a major global public health problem, with a continuously rising incidence of newly diagnosed cases. Effective prevention and control of diabetes have therefore become critical public health goals. Previous studies have shown that self-management, when combined with family support, is associated with improved health behaviors among both patients diagnosed with diabetes and those at risk. This is particularly evident in behavioral modifications related to dietary control, physical activity, and stress management, which contribute to reductions in body mass index and better glycemic control. Patients suspected of having diabetes represent a group undergoing diagnostic evaluation, with outcomes potentially confirming either a diagnosis of diabetes or identifying them as at-risk. Enhancing self-management practices during this transitional phase, supported by family participation, may facilitate positive behavioral changes, reduce the likelihood of progression to diabetes, and support disease control in those who are subsequently diagnosed. Objective To examine the effects of a family self-management enhancement program on knowledge of diabetes prevention, family support, self-management behaviors for diabetes prevention, body mass index, and blood glucose levels in patients suspected of having diabetes mellitus. Design This study employed a quasi-experimental design with two-group pre- and post-tests. It applied the self-management framework of Ryan and Sawin, which integrates both contextual and process dimensions. The contextual dimension involved assessing current health behaviors, risk factors, and the family’s potential to provide support. The process dimension included activities aimed at enhancing knowledge and self-management skills related to diet, physical activity, and stress management, all facilitated through family support. Monitoring and evaluation mechanisms were incorporated to ensure short-term outcomes, specifically behavioral changes in food consumption, exercise, and stress management. These changes are expected to lead to long-term outcomes, including reductions in body mass index and blood glucose levels, thereby decreasing the risk of developing diabetes. Methodology The study sample consisted of 70 patients suspected of having diabetes in Chaiyaphum Province. Participants were selected through simple random sampling according to inclusion and exclusion criteria, and were assigned equally to the experimental and control groups (35 participants per group). The sample size was determined using G*Power software, with an effect size of 0.80 derived from a previous study and a power of .90. Researchers designated specific community areas for the experimental and control groups, followed by random sampling within each area. The research instruments, developed by the researchers, comprised two main components: 1) an 8-week family self-management enhancement program, which included five workshop sessions, two of which (sessions 2 and 4) involved family participation. The program also incorporated exercise training using music-based stick dancing and weekly follow-up via the LINE application by family members throughout the intervention period; and 2) data collection tools divided into five sections: (1) general information, (2) knowledge on diabetes prevention, (3) family support, (4) self-management behaviors for diabetes prevention, and (5) clinical assessments including weight, height, and fingertip blood glucose levels. The content validity index (CVI) for both the program and each questionnaire was equally 1.00. Reliability testing yielded a KR-20 coefficient of .82 for the diabetes prevention knowledge questionnaire, and Cronbach’s alpha coefficients of .86 and .89 for the family support and self-management behavior questionnaires, respectively. Data collection was conducted from December 2024 to February 2025. Descriptive statistics, Independent t-tests, and Paired t-tests were used for data analysis. Results The experimental and control groups did not differ significantly in terms of general and health-related characteristics. The mean age of participants was 57.40 years (SD = 3.35) in the experimental group and 57.94 years (SD = 4.45) in the control group. After participating in the program, the experimental group had significantly higher overall and sub-scale knowledge of diabetes prevention compared to the control group (t = 7.156, p < .001) and to baseline scores (t = -9.367, p < .001). Family support for diabetes prevention was also significantly greater in the experimental group than in the control group (t = 10.957, p < .001) and showed a significant higher from baseline (t = -11.580, p < .001). Similarly, self-management behaviors related to diabetes prevention were significantly higher in the experimental group than in the control group (t = 17.024, p < .001) and improved significantly from the baseline (t = -20.922, p < .001). In terms of clinical outcomes, the experimental group exhibited significantly lower body mass index (BMI) compared to the control group (t = -3.100, p = .003) and the baseline (t = 7.425, p < .001). Blood glucose levels were also significantly lower in the experimental group than in the control group (t = -5.431, p < .001) and showed a significant lower than the baseline (t = -7.395, p < .001). Recommendation Nurses and multidisciplinary teams involved in the care of patients suspected of having diabetes may adopt the family self-management enhancement program, particularly its components focused on enhancing knowledge and beliefs about diabetes, enhancing self-regulation skills, and promoting family participation in diabetes prevention, for use among target populations with similar contextual characteristics.